2018
DOI: 10.1038/s41467-017-02731-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chitinase-3-like-1 in T cell elicits Th1 and cytotoxic responses to inhibit lung metastasis

Abstract: Chitinase-3-like-1 (Chi3l1) is known to play a significant role in the pathogenesis of Type 2 inflammation and cancer. However, the function of Chi3l1 in T cell and its clinical implications are largely unknown. Here we show that Chi3l1 expression was increased in activated T cells, especially in Th2 cells. In addition, Chi3l1-deficient T cells are hyper-responsive to TcR stimulation and are prone to differentiating into Th1 cells. Chi3l1-deficient Th1 cells show increased expression of anti-tumor immunity gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 55 publications
4
76
0
1
Order By: Relevance
“…In our murine model of AD induced by OVA, CHI3L1 deficiency resulted in the attenuation of allergic skin inflammation and was accompanied by low Th2 cytokine levels and effector CD4 + T cell populations, suggesting that CHI3L1 promotes Th2 immune responses. Consistent with this finding, a recent study demonstrated that BRP‐39 −/− CD4 + T cells are prone to Th1 differentiation, and that they show reduced Th2 differentiation via an IFNγ signalling pathway . Additionally, in the absence of CHI3L1, IL‐18‐induced pulmonary inflammatory responses were significantly ameliorated by downregulation of Th2 and Th17 responses …”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In our murine model of AD induced by OVA, CHI3L1 deficiency resulted in the attenuation of allergic skin inflammation and was accompanied by low Th2 cytokine levels and effector CD4 + T cell populations, suggesting that CHI3L1 promotes Th2 immune responses. Consistent with this finding, a recent study demonstrated that BRP‐39 −/− CD4 + T cells are prone to Th1 differentiation, and that they show reduced Th2 differentiation via an IFNγ signalling pathway . Additionally, in the absence of CHI3L1, IL‐18‐induced pulmonary inflammatory responses were significantly ameliorated by downregulation of Th2 and Th17 responses …”
Section: Discussionsupporting
confidence: 61%
“…35 pathway. 36 Additionally, in the absence of CHI3L1, IL-18-induced pulmonary inflammatory responses were significantly ameliorated by downregulation of Th2 and Th17 responses. 37,38 CHI3L1 is widely recognized as an important regulator of both M2 macrophage activation and Th2 inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…Chitinase 3-like-1 (Chi3L1), also called a breast regression protein 39 (BRP-39) in mouse and YKL-40 in human, is known as a secreted glycoprotein and prototypic mammalian chitinase like protein [11,12]. Increased expression of Chi3L1 protein and mRNA have been shown in various disease models and states including rheumatoid arthritis schizophrenics, inflammatory bowel disease, chronic obstructive pulmonary disease, asthma, diabetes, and atherosclerosis [13][14][15][16][17][18][19], Especially, Chi3L1 expression has been found in a variety of cancer cells such as breast, lung, prostate, colon, rectum, ovary, kidney, breast, glioblastomas, and malignant melanoma [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Rather, they appear to have evolved to play a role in the development and progression of Th2 immune responses and in defence against parasitic infections and cancer (54)(55)(56). Chitinase-like proteins are expressed by macrophages and T cells and are involved in lung inflammation, remodelling and fibrosis (35,36) and CHIT1 and CHI3L1 have previously been shown to be induced in alveolar macrophages during mycobacterial infection (30). Other genes upregulated in discarded lungs included SLC7A5 and GBP5.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, serum CHIT1 has been investigated as a biomarker of disease severity and progression in several lung diseases, including chronic obstructive pulmonary disease (34). Chitinase-like proteins (including CHI3L1) are expressed by alveolar macrophages and play a role in lung inflammation, remodeling and fibrosis (35,36). Of note, SLC7A5 (an amino acid transporter) and GBP5 (Guanylate-binding protein 5) promote NLRP3 inflammasome activation and IL1ß production in monocytes and macrophages (37,38).…”
Section: Lungs Deemed Unusable Have Increased Induction Of Immune Patmentioning
confidence: 99%